Dampak Psikologis Berbusana Muslimah Terhadap Kesadaran Dan Perilaku Sosial Keagamaan - Saeful Malik (Lembaga Penerbitan dan Publikasi Ilmiah IAI Bunga Bangsa Cirebon, 2021)
This research was backgrounded by a thought that ideally, IAIN Syekh Nurjati Cirebon coed which applying muslimat’s dresses comprehend that jilbab which is imposed in everyday appearance contain psychological consequence to grow religious awareness and religious social behavior. This research aim to: (1) To find out the understanding and perception of IAIN Syekh Nurjati Cirebon coed about jilbab, as the manifestation of muslimat’s dresses; (2) to describe the feeling of IAIN Syekh Nurjati Cirebon coed when they used the muslimat’s dresses; (3) To proof whether is or there isn’t, any psychological impact of usage muslimat’s dresses and “jilbab gaul” among IAIN Syekh Nurjati Cirebon’s coed to its social behavior and religious awareness among them. From the result of research can be concluded that most ( 66,66 %) IAIN Syekh Nurjati Cirebon coed still comprehend jilbab as understanding of common public, namely jilbab interpreted only as veil, that is cloth covering on head or khimar (in Arabic language), in average ( 96,6 %) coed imposing muslimat’s dresses - as according to its understanding – suggest that to feel to be comfortable and more self confidence when imposing jilbab, though feel to be comfortable and the self confidence arise from different reason. Psychological implication of muslimat’s dresses usage to some small part ( 33,33%) of IAIN Syekh Nurjati Cirebon’s coed specially who imposing wide jilbab, better able to have a command over and back from deeds (akhlâq) which prohibited by religion and other wickedness. As for to most (66,66%) other coeds, specially coeds which wear “jilbab gaul”, their behavior in social intercourse tend to follow behavior of